The Influence of UKI’s Tagline “UKI HEBAT” in Forming the Characters of UKI’s People to be “HEBAT” - Mesta Limbong; Yules Orlando Sianipar; Iosephine Sere G (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2022)
Through the tagline “UKI HEBAT”, the Head of the University and his staff hope that educators, staff, and other workers, as well as students, understand what the purpose of their work plan is and make the character of UKI people become “HEBAT, and the Universitas Kristen Indonesia (UKI) becomes better. better than other universities. The background of this research is to see the influence of the tagline through the Psycholinguistics-Cybernetic model in providing a "self-image" of its workers and students and shaping their character to be "HEBAT". Psycholinguistics-Cybernetics is an interdisciplinary study, involving the disciplines of linguistics and psycho-cybernetics. The research sample is people in the UKI environment who had heard the tagline "UKI HEBAT" for at least 1 year. This research is quantitative research. Data was obtained by using a survey method using a questionnaire. This study used two variables, the independent variable in this study was the tagline of the Indonesian Christian University (UKI), "UKI HEBAT" which is symbolized by X. The dependent variable in this study was the awareness of the Indonesian Christian University (UKI) people on the tagline which is symbolized by Y. With the use of the tagline "UKI Great" it can be seen that there is a significant influence in character building among Indonesian Christian University (UKI) people. This result strengthens the Psycholinguistics-Cybernetics theory that character-forming speech is true.